2010
DOI: 10.1557/mrs2010.613
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Natural Space Environment and ESA, JAXA, and NASA Materials Flight Experiments

Abstract: velocity. Technology improvements allow higher resolution measurements; computing efficiency provides higher precision modeling; and our understanding of the space environment constituency improves. This overview will provide a general description of the space environment and point to some key features that spacecraft designers need to consider to reduce risk and improve engineering performance. The best metric that spacecraft designers can use to assess the engineering performance of the spacecraft is to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…When deployed in low Earth Orbit (LEO), satellites are particularly prone to AO exposure (with kinetic energy of 5eV, nominal AO flux of around 10 14 -10 15 atoms/ cm 2 s), which plays a major role in the degradation of polymer based composite materials [3]. Several in-orbit tests have been performed by the European Space Agency (ESA) [4], Japan Aerospace Exploration Agency (JAXA), and the National Aeronautics and Space Administration (NASA) [5e8], to understand the AO resistance of various materials, and these have been reviewed [9]. Extensive research has been undertaken to investigate the AO resistance of composite materials using ground-based facilities, but few publications focus on the AO behaviour of space-qualified composites that are already used in orbit.…”
Section: Introductionmentioning
confidence: 99%
“…When deployed in low Earth Orbit (LEO), satellites are particularly prone to AO exposure (with kinetic energy of 5eV, nominal AO flux of around 10 14 -10 15 atoms/ cm 2 s), which plays a major role in the degradation of polymer based composite materials [3]. Several in-orbit tests have been performed by the European Space Agency (ESA) [4], Japan Aerospace Exploration Agency (JAXA), and the National Aeronautics and Space Administration (NASA) [5e8], to understand the AO resistance of various materials, and these have been reviewed [9]. Extensive research has been undertaken to investigate the AO resistance of composite materials using ground-based facilities, but few publications focus on the AO behaviour of space-qualified composites that are already used in orbit.…”
Section: Introductionmentioning
confidence: 99%
“…In the LEO circumstance, the space effect on materials is very severe and complex because of the synergistic interaction of orbital environments such as high-energy radiation particles, atomic oxygen, micrometeoroids, orbital debris, and ultraviolet irradiation interacting synergistically, along with thermal exposure . It was reported that AO fluence in LEO was from 1 × 10 12 to ∼1 × 10 15 atom cm –2 s –1 , and exposure of 2.0 × 10 20 atom cm –2 was roughly equivalent to 6 months exposure to AO in an LEO circumstance .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, piezoceramic transducers for sonic and ultrasonic NDT may generate spurious signals or noise from pyroelectric effects, if exposed to temperature changes in time (388). Spacecraft are exposed to an even more complex environment (389), and designing and developing durable SHM systems for reliable, long-term monitoring of these is a considerable challenge.…”
Section: Ndt or Nde Of Pmc And Shm In Aerospace Applicationsmentioning
confidence: 99%